Effects of resistance training on the performance of activities of daily living in patients with Alzheimer's disease - Garuffi, Marcelo [UNESP]; Costa, José Luiz Riani [UNESP]; Hernández, Salma Sthephany Soleman [UNESP]; Vital, Thays Martins [UNESP]; Stein, Angelica Miki [UNESP]; Santos, Julimara Gomes dos [UNESP]; Stella, Florindo [UNESP] (Wiley, 2013)
Aim: The objective of this study was to investigate the effects of resistance training in activities of daily living performance in Alzheimer's disease (AD) patients. Methods: An exploratory and longitudinal study, lasting for 16weeks, with the participation of 34 patients divided equally in: the training group (TG), who participated in a resistance training protocol (three sets of 20 repetitions in five exercises); and the social gathering group (SGG), who participated in a social interaction protocol (i.e. group dynamics, writing and reading activities). Results: We observed significant differences between the groups in moving around the house, climbing stairs, standing up from the floor and putting on socks tests. Conclusion: This study showed that resistance training improves agility, lower limb strength, balance and flexibility in AD patients, while SGG protocol is important to improve the agility. © 2012 Japan Geriatrics Society.
Keywords: Activities of daily living; Aged; Alzheimer disease; Motor activity; Resistance training; adolescent; climbing; clinical article; daily life activity; disease severity; exercise; female; group dynamics; human; longitudinal study; male; priority journal; reading; resistance training; social interaction; standing; writing